2018
DOI: 10.1038/s41467-018-04956-5
|View full text |Cite|
|
Sign up to set email alerts
|

Long-haul optical transmission link using low-noise phase-sensitive amplifiers

Abstract: The capacity and reach of long-haul fiber optical communication systems is limited by in-line amplifier noise and fiber nonlinearities. Phase-sensitive amplifiers add 6 dB less noise than conventional phase-insensitive amplifiers, such as erbium-doped fiber amplifiers, and they can provide nonlinearity mitigation after each span. Realizing a long-haul transmission link with in-line phase-sensitive amplifiers providing simultaneous low-noise amplification and nonlinearity mitigation is challenging and to date n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 44 publications
0
35
1
4
Order By: Relevance
“…It has been experimentally shown that a single-channel and single polarization two-mode PSA link at lower transmission speeds, such as 10 GBaud, can result in a remarkable transmission distance improvement of 5.6 times if a PSA link is used instead of an in-line dispersion managed PIA link [11]. However, our simulation study shows that at higher transmission speeds, such as 28 GBaud, a PSA ability to provide a significantly better transmission performance compared to a PIA link in a single-span transmission scenario, does appear to not hold anymore.…”
Section: Necessity Of Multi-span Dispersion Map Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been experimentally shown that a single-channel and single polarization two-mode PSA link at lower transmission speeds, such as 10 GBaud, can result in a remarkable transmission distance improvement of 5.6 times if a PSA link is used instead of an in-line dispersion managed PIA link [11]. However, our simulation study shows that at higher transmission speeds, such as 28 GBaud, a PSA ability to provide a significantly better transmission performance compared to a PIA link in a single-span transmission scenario, does appear to not hold anymore.…”
Section: Necessity Of Multi-span Dispersion Map Optimizationmentioning
confidence: 99%
“…regarding the dispersion map optimization for in-line dispersion compensated PIA links has been carried out [18][19][20], but these principles are not directly applicable to PSA links, since the effectiveness of the nonlinearity mitigation in PSA links is highly dependent on correlation properties of propagated signal and idler waves. It has been shown previously that the dispersion management for a single-span dispersion map optimized PSA link [2,11,21] and for a two-span dispersion map optimized PSA link [22] plays an important role for the nonlinearity mitigation performance. The importance of dispersion map optimization for twin-waves was first noted in [13], where according to the first-order perturbation theory, a symmetric span power map with an anti-symmetric dispersion map should be used for the best nonlinearity mitigation performance for the PCTW approach.…”
mentioning
confidence: 99%
“…Recently, WDM amplification and an SNR advantage of around 5 dB compared with EDFAs have > REPLACE THIS LINE WITH YOUR PAPER IDENTIFICATION NUMBER (DOUBLE-CLICK HERE TO EDIT) < 2 been demonstrated using PPLN waveguides and HNLFs [14][15][16]. The potential of ND-PSAs as inline amplifiers has also been demonstrated [17]. One of the most important problems we face in actual PSAs is the effect of chromatic dispersion (CD) on the gain spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…A PSA that can amplify both quadratures of an optical wave requires two input waves at different wavelengths, the signal and its conjugate (idler) and a single pump. Although PSAs are available in many different configurations, the one-pump non-degenerate signal/idler configuration, which is simple to implement and amplifies both light quadratures 17 , was adopted in this work.…”
Section: Introductionmentioning
confidence: 99%